Insights from the front line: uplifting stories of the COVID-19 pandemic through the eyes of the public health workforce in Iowa - Haines, Heidi; Sursely, Amanda; Pham, Hanh; Beltran, Rylee; Sewell, Daniel K.; Reinders, Lina Tucker; Askelson, Natoshia; Dixon, Sarah; Emrich, Kaitlin; Estle, Christine; Lewis, Michelle; Parker, Edith; et al. (Frontiers in Public Health, 2025)
IntroductionSARS-CoV-2 was declared a pandemic in March 2020. Studies have characterized some of the negative impact of the pandemic on public health workers (PHW), but few have explored the strength and coping strategies used. Our study documents the experiences of PHW in Iowa during the pandemic.MethodsWe used an innovative mixed methods data collection tool, SenseMaker® to gather stories from PHW in Iowa between March and July 2022. Participants provided additional data about their story via structured follow-up questions. We conducted descriptive analyses of the quantitative questions. A qualitative thematic and sentiment analysis was applied to all stories.ResultsThe final sample size was 163 stories. PHW who submitted stories identified as mostly white (93.9%), and women (83.4%). Respondents were most likely to feel that in the story they told: the ability to act was out of their control; the strongest influence was from political considerations; decisions were made out of necessity; they wished for more focus on evidence-based public health. PHW were most likely to describe their emotional state at the height of the pandemic as frustration (61%), uncertainty (55%), and helplessness (50%). Those who felt in control were more likely to express positive emotions. Qualitative thematic analysis of these stories revealed 8 themes, highlighting facilitators (e.g., strong partnerships and collaborations) and barriers (e.g., politicization and controversial government response) to effective pandemic response.DiscussionThe stories PHW shared powerfully illustrate the context of the pandemic in Iowa, a state that spent the least time under high stringency policies.